The Facts on File companion to the American short story - Werlock, Abby H. P.; Facts on File, Inc. (New York : Facts on File, 2000)
"A handy volume that presents an immediate introduction to American short fiction from the 19th century to the 1990s, the 675 alphabetically arranged entries consist of author biographies, literary terms, theories, themes, well-known characters, influential events, and summaries of major stories. Entries are definitive and written in a clear style."--"Outstanding Reference Sources," American Libraries, May 2001.
Includes bibliographical references and index.
Keywords: Short stories, American -- Encyclopedias